Analisis Pengaruh Karakteristik Perusahaan Terhadap Audit Report Lag Tahun 2019-2020 - Evani Larisa, Susanto Salim (Jurnal Ekonomi, 2021)
The purpose of this empirical study is to find out the influence of company internal factors on audit report lag with manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2020 period. Sample method used is purposive sampling and produce 98 companies that met the criteria. The research data type is secondary data which came from annual financial reports and annual reports on the official website of the Indonesia Stock Exchange. This research using IBM SPSS version 24 software as data processing. The results of this empirical study were found that company size and complexity significantly affect audit report lag. As well as the profitability and solvency variables have no significant effect on audit report lag.